(untitled) (Journal of Contemporary Philology, 2020)
The paper, at the outset, examines the data regarding Calvino’s participation in the Second World War, aiming to understand the ways in which the author’s traumatic experience is introduced in his first works, maybe too hastily defined by the author himself as Neorealist. We are referring to his three short stories published in the collection Last Comes the Raven (Einaudi, 1949), as well as to his first novel The Path to the Nest of Spiders (Einaudi, 1947). Further on, the paper follows the ideological and literary maturation of the young Calvino (born in 1923), following a path that leads from anarchism to communism, as well the author’s ideas related to violence, history and the commitment of the intellectual. We are also examining the narratological elements in the novel, especially regarding the choice of the narrator, as well as the ideological element contained in the ninth chapter of the work where, imagining a dialogue between an intellectual and a worker, the author analyses the partisans – antiheroes in his novel – whose accumulated rage could take them to the other, the fascist side. Following his non-orthodox choice to represent the partisans as antiheroes, Calvino implies the difficulty lying before the people, weak and imperfect themselves, in all parts of the world contaminated by war, in their struggle to choose the right side in a period of total chaos and propaganda.